OCULAR MANIFESTATIONS OF APLASTIC ANEMIA FOLLOWING PLATELET TRASFUSION: A CASE REPORT - S., Divyalakshmi K.; N., Kalpana B. (Journal of Health and Allied Sciences NU, 2014)
Aplastic anaemia is a rare haemopoietic stem-cell disorder that results in pancytopenia and hypocellular bone marrow. Ocular findings are manifestations of preexisting anemia. Here we are reporting a case of aplastic anemia which presented with the ocular findings following platelet transfusion which has not been reported in literature to the best of our knowledge.
Keywords: Aplastic anemia; platelet transfusion; ocular manifestations